It matters how to recall – task differences in retrieval practice - Endres, Tino; Kranzdorf, Lena; Schneider, Vivien; Renkl, Alexander (Instructional science, 2020)
The type of a recall task may substantially influence the effects of learning by retrieval practice. In a within-subject design, 54 university students studied two expository texts, followed by retrieval practice with either short-answer tasks (targeted retrieval) or a free-recall task (holistic retrieval). Concerning the direct effects of retrieval practice, short-answer tasks led to increased retention of directly retrieved targeted information from the learning contents, whereas free-recall tasks led to better retention of further information from the learning contents. Concerning indirect effects, short-answer tasks improved metacognitive calibration; free-recall tasks increased self-efficacy and situational interest. These findings confirm the assumption that the effects of retrieval practice depend on the type of recall task: short-answer tasks help us remember targeted information units and foster metacognitive calibration. Free-recall tasks help us remember a broader spectrum of information, and they foster motivational factors.